ISU SEKSISME DAN RELASI GENDER DALAM KEPEMIMPINAN PEREMPUAN DI ORGANISASI MAHASISWA UNIVERSITAS DIPONEGORO - Shafa Amanda, Karina; Rahardjo, Turnomo; Qurrota Ayun, Primada (Interaksi Online, 2024)
The existence of women in society is still strongly entrenched as women are seen as weak individuals and are not trusted to do work outside of the domestic sphere. Among student organization structures, men are considered more appropriate to make decisions because leadership is often associated with masculine values, such as being competitive and aggressive in public life. Women should be considered as rational beings with the same abilities and rights as men, and can position themselves as leaders based on their ability to lead. This study aims to determine the issue of sexism and gender relations in women's leadership in Diponegoro University student organizations. The theories used are Feminist Viewpoint Theory, Gender Role Theory, and Leadership Theory. This research uses an interpretive paradigm with a phenomenological approach, as well as in-depth interview data collection techniques conducted on five individuals